PERBANDINGAN LUARAN KLINIS SETELAH TINDAKAN CORONARY ARTERY BYPASS GRAFTING (CABG) DENGAN PERCUTANEOUS CORONARY INTERVENTION (PCI) PADA PASIEN CORONARY ARTERY DISEASE (CAD) DENGAN GANGGUAN FUNGSI GINJAL : SYSTEMATIC REVIEW - Dhiya Putri Aqilah Sandha (2023)
According to WHO data, heart disease is still the leading cause of death, and has described CAD is the leading cause of death worldwide. The 2018 Riskesdas shows that the prevalence of heart disease, including CAD, based on doctors' diagnoses in Indonesia is 1,5%. Management measures in CAD patients are CABG or PCI. The research design used in this study was a literature review using a systematic review method. A systematic literature review regarding comparing CABG and PCI costs is needed to determine optimal therapeutic options in CAD patients. A literature search was conducted on four different databases, namely PubMed, SagePub, Google Scholar, and Science Direct, published within the last 10 years. A literature review was carried out based on the Preferred Reporting Items for Systematic Review and Meta-Analyses Protocol (PRISMA-P) 2020 protocol. A total of eight literatures met the study inclusion and exclusion criteria. There are five literatures stating that CABG is better, two other literatures stating that there is no significant post-rehabilitation difference between CABG and PCI, and one literature stating that PCI has better survival after 5 years in CAD patients with impaired renal function. CABG is considered more effective and is recommended as the primary treatment option in CAD patients with kidney disorder. Nevertheless, PCI can still be used as an alternative therapy in CAD patients by considering kidney function and comorbid diseases.